2018
DOI: 10.1519/jsc.0000000000002048
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Moderate- Versus High-Load Resistance Training on Muscle Growth, Body Composition, and Performance in Collegiate Women

Abstract: Cholewa, JM, Rossi, FE, MacDonald, C, Hewins, A, Gallo, S, Micenski, A, Norton, L, and Campbell, BI. The effects of moderate- versus high-load resistance training on muscle growth, body composition, and performance in collegiate women. J Strength Cond Res 32(6): 1511-1524, 2018-Twenty young women (20.3 + 1.5 years, 164 + 6 cm, 68.7 + 13.8 kg) without prior structured resistance training experience were recruited for this study. Body composition (BodPod), compartmental water (Bioelectrical Impedance), 7-site sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…Seventeen studies compared low- versus high-load resistance training ( 2 , 5 , 6 , 33 , 34 , 36 , 38 , 39 , 42 46 , 49 51 , 53 ), four compared low- versus moderate-load ( 35 , 40 , 47 , 52 ), five compared moderate- versus high-load ( 7 , 32 , 37 , 41 , 48 ), and two studies compared low- versus moderate- versus high-load ( 3 , 4 ). Most of the studies involved men (19 of 28, or 67.9% [ 2 – 7 , 34 , 38 42 , 44 48 , 53 ]) and untrained participants (21 of 28, or 75.0% [ 2 6 , 32 39 , 42 , 44 46 , 49 52 ]; Table S2, Supplemental Digital Content 2, characteristics of included studies, http://links.lww.com/MSS/C234 ). None of the studies included highly strength-trained individuals as defined by 1-RM test values reported in studies involving elite athletes (average relative strength of 2.0 body weights for back squat and 1.5 body weights for bench press ( 55 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies compared low- versus high-load resistance training ( 2 , 5 , 6 , 33 , 34 , 36 , 38 , 39 , 42 46 , 49 51 , 53 ), four compared low- versus moderate-load ( 35 , 40 , 47 , 52 ), five compared moderate- versus high-load ( 7 , 32 , 37 , 41 , 48 ), and two studies compared low- versus moderate- versus high-load ( 3 , 4 ). Most of the studies involved men (19 of 28, or 67.9% [ 2 – 7 , 34 , 38 42 , 44 48 , 53 ]) and untrained participants (21 of 28, or 75.0% [ 2 6 , 32 39 , 42 , 44 46 , 49 52 ]; Table S2, Supplemental Digital Content 2, characteristics of included studies, http://links.lww.com/MSS/C234 ). None of the studies included highly strength-trained individuals as defined by 1-RM test values reported in studies involving elite athletes (average relative strength of 2.0 body weights for back squat and 1.5 body weights for bench press ( 55 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the assessments, muscle hypertrophy was assessed for the lower limbs in 15 studies ( 3 – 7 , 32 , 35 39 , 43 , 44 , 49 , 50 ), followed by 8 studies assessing the upper limbs ( 4 , 7 , 32 , 34 , 45 , 47 , 48 , 50 ) and 5 studies assessing the whole body (e.g., dual-energy x-ray absorptiometry) ( 33 , 40 , 42 , 46 , 53 ), whereas lower-body muscle strength was assessed in 20 studies ( 3 – 7 , 32 , 33 , 35 , 38 44 , 46 , 48 , 50 52 ), followed by 12 studies assessing upper-body muscle strength ( 2 , 4 , 7 , 33 , 40 , 41 , 43 , 45 , 47 , 48 , 50 , 51 ), all using the 1-RM test. Eighteen studies reported the total volume performed during the intervention ( 4 , 5 , 7 , 32 35 , 37 45 , 48 , 50 ). The number of studies among the resistance training loads for muscle hypertrophy and muscle strength is shown in the network geometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in neuromuscular function through aerobic exercise is associated with other health benefits, including reduced lower-back pain ( Cortell-Tormo et al, 2018 ), enhanced bone density ( Petersen et al, 2017 ), better body composition ( Cholewa et al, 2017 ) and more favorable psychological perception (e.g., self-satisfaction, self-esteem and body image) ( Sothern et al, 1999 ). In this context, short-term (i.e., 4-week) resistance training has been proven to improve the one-repetition concentric strength of sedentary, healthy men by 19% ( Raue et al, 2005 ), as well as to elevate the maximal isometric torque of both healthy men and women ( Mayhew et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Resistance training is an effective method of conditioning to enhance muscle strength (ie, ability to generate muscle force), while also promoting other health-related benefits including increased bone mass and muscle cross-sectional area, as well as decreased body fat and blood pressure in females. 1,3 As such, re- Increased interest has emerged in quantifying cardiac morphology and function in resistance-trained male athletes [3][4][5][6] to understand specific adaptations and potential negative responses to resistance training protocols. For instance, a review by Haykowsky et al 3 revealed intense dynamic and isometric resistance training increases concentric left ventricular (LV) hypertrophy, which is characterized by an increase in LV mass with an augmented ratio of wall thickness to LV diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training has gained increased popularity among females in recent years 1,2 . Resistance training is an effective method of conditioning to enhance muscle strength (ie, ability to generate muscle force), while also promoting other health‐related benefits including increased bone mass and muscle cross‐sectional area, as well as decreased body fat and blood pressure in females 1,3 . As such, resistance training is of interest for competitive female athletes such as bodybuilders, powerlifters, and Olympic weightlifters, as well as the fitness‐oriented portion of the general population.…”
Section: Introductionmentioning
confidence: 99%